BIOPHILIC ARCHITECTURE AS A PREVENTIVE STRATEGY FOR YOUTH MENTAL HEALTH IN URBAN CENTERS - Wahyu Abdillah; Elias Nicolaus Simbolon (CV. Denasya Smart Publisher, 2026)
Urban youth increasingly face mental health challenges due to academic pressure, sedentary lifestyles, limited access to safe public spaces, and the psychological impacts of dense urban environments. Conventional approaches to youth mental health, which are largely clinical or institutional, often fail to address preventive and environmental dimensions of well-being. In response, this paper examines the potential role of biophilic architecture as a non-clinical and preventive strategy to support youth mental health in urban contexts, particularly within sport and youth centers. This study employs a qualitative literature-based approach, synthesizing psychological theories, empirical studies, and architectural research related to biophilic design, adolescent mental health, and the built environment. The findings indicate that biophilic design elements such as natural lighting, ventilation, green and blue elements, spatial openness, and sensory-friendly environments are associated with stress reduction, improved mood, enhanced emotional regulation, and increased place attachment among adolescents. Sport and youth centers, when designed with biophilic principles, can function not only as physical activity hubs but also as restorative social infrastructures that support mental well-being. The paper identifies a research gap in youth-specific, urban-based studies that integrate biophilic design with real architectural typologies. By positioning biophilic architecture as a preventive mental health strategy, this study contributes to architectural discourse and youth studies, emphasizing the importance of everyday environments in fostering psychological resilience among urban youth, particularly in developing city contexts.